Book Theft as Social Deviance in Modern China: An Elegant Offense or the Intellectual Robin Hood - Guo, Yi (Javnost-The Public, 2024)
During China’s transition from pre-modern to modern society, book theft, as a form of social deviance, reflected the multifaceted cultural metaphors of books in modern Chinese social life. The shift from the notion that “common thieves do not steal books” to book theft as a representation of cultural power struggles exemplifies the media cultural transformation in modern Chinese society. Contemporary attitudes towards book theft reveal complex tensions between economic order, publishing supply and demand, social mentality, cultural capital, knowledge power, media discourse, and public opinion during this period of societal change. In this context, book theft can be seen as a dual phenomenon, embodying both a clever and sophisticated act that challenges dominant norms and values on one hand, and a form of rebellion that seeks to redistribute power and knowledge, akin to the legendary outlaw Robin Hood, on the other.